Development of Collaborative Blended Learning Instructional Model Based on the ADDIE Framework to Foster Analytical Writing Skills - Ernitasari Mulyadi; Rahayu Prasetyaningsih; Andi Idayani; Ismail Managkari; Mukhlis Lubis (Journal La Edusci, 2026)
This study explores the implementation of a collaborative blended learning model for teaching English analytical exposition texts. The model was developed using the ADDIE framework, which consists of the stages of analysis, design, development, implementation, and evaluation. The study addresses challenges faced by students, such as difficulties in individual writing tasks and limited experience with collaborative learning. Through a combination of online and offline activities, including the use of digital tools such as Padlet, the collaborative blended learning model encourages interactive group discussions and peer feedback to enhance students’ writing skills. The findings indicate a significant improvement in students’ writing performance, motivation, and engagement. The developed model also provides an interactive learning environment that facilitates deeper collaboration and active participation among students. This study underscores the potential of integrating collaborative blended learning into writing instruction to address students’ challenges and improve learning outcomes.